2013
DOI: 10.1016/j.neubiorev.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in resisting temptation: Implications for addiction

Abstract: When exposed to the sights, sounds, smells and/or places that have been associated with rewards, such as food or drugs, some individuals have difficulty resisting the temptation to seek out and consume them. Others have less difficulty restraining themselves. Thus, Pavlovian reward cues may motivate maladaptive patterns of behavior to a greater extent in some individuals than in others. We are just beginning to understand the factors underlying individual differences in the extent to which reward cues acquire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 407 publications
(553 reference statements)
5
153
0
Order By: Relevance
“…There is considerable evidence that, relative to GTs, STs attribute greater incentive salience to discrete localizable cues associated with either food or cocaine reward, assessed using a variety of procedures Saunders and Robinson, 2013a). Of particular importance, both discrete and interoceptive cues are more effective in evoking conditioned motivation ('wanting') for cocaine in STs than GTs Saunders et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is considerable evidence that, relative to GTs, STs attribute greater incentive salience to discrete localizable cues associated with either food or cocaine reward, assessed using a variety of procedures Saunders and Robinson, 2013a). Of particular importance, both discrete and interoceptive cues are more effective in evoking conditioned motivation ('wanting') for cocaine in STs than GTs Saunders et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that it is possible to predict, based on the tendency to attribute incentive salience to a discrete food cue, and before any drug experience, which animals will show the highest likelihood of cue-induced relapse/reinstatement Saunders and Robinson, 2013a). Based on these studies, we suggested that STs may be especially vulnerable to addiction Saunders and Robinson, 2013a).…”
Section: Implications For Thinking About Individual Differences In Thmentioning
confidence: 94%
See 2 more Smart Citations
“…The underlying associations continue to be present and can re-emerge, either spontaneously or in response to a cue. Interestingly, context-induced reinstatement is more prominent in goal-than in sign-trackers (Saunders and Robinson, 2013). Moreover, a context paired with ethanol injections can immediately and profoundly impair the ability to exert goal-directed control (Ostlund et al, 2010), and optogenetic suppression or activation of the prelimbic cortex, which is thought to involve goaldirected computations, can abolish or re-establish sensitivity to punishments (Chen et al, 2013).…”
Section: Shifts Towards Model-free Learning In Addictionmentioning
confidence: 99%